2020
DOI: 10.1101/2020.10.19.344077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive deletion landscape of CRISPR-Cas9 identifies minimal RNA-guided DNA-binding modules

Abstract: Proteins evolve through the modular rearrangement of elements known as domains. It is hypothesized that extant, multidomain proteins are the result of domain accretion, but there has been limited experimental validation of this idea. Here, we introduce a technique for genetic minimization by iterative size-exclusion and recombination (MISER) that comprehensively assays all possible deletions of a protein. Using MISER, we generated a deletion landscape for the CRISPR protein Cas9. We found that Cas9 can tolerat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Deletion of the entire BH severely reduced the catalytic activity. Similarly, a BH deletion variant of SpyCas9 was inactive ( 58 ). This shows that the BH is an essential segment for both enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the entire BH severely reduced the catalytic activity. Similarly, a BH deletion variant of SpyCas9 was inactive ( 58 ). This shows that the BH is an essential segment for both enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, DMS has been applied, for instance, to characterize human disease mutations (2), dissect protein-coding regions in the adeno-associated virus genome (3) and investigate the mutational fitness landscape of CRISPR-Cas9 (4,5). Moreover, comprehensive DMS datasets comprising protein single and double mutants were used for detailed analysis of intramolecular interactions, based on which the three-dimensional protein structure could be inferred (6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fine-tuning the expression of BEs and sgRNAs by using the optimal combination of promoters is a crucial factor in minimizing the toxic effects in the IRI-CCE platform. A recent study [44] indicated that the sufficiently perturbed dsDNA in bacteria-during replication, transcription, or other rearrangements-provides enough opportunity for Cas9 binding to a target site in the form of dynamically stretched single-strand DNA (ssDNA) or un-and underwound doublestrand DNA. Therefore, it is conceivable that the fewer nCas9-BE enzyme molecules, mainly evolved versions with a faster catalytic rate [18,45], produced by p35S-based promoters are enough to show relatively higher deamination activity.…”
Section: Discussionmentioning
confidence: 99%